The Pathogenesis of Candida Infections in a Human Skin Model: Scanning Electron Microscope Observations. (5th September 2011) - Raz-Pasteur, A.; Ullmann, Y.; Berdicevsky, I.
Abstract : Cutaneous candidiasis is an opportunistic infection that arises, in most cases, from endogenous, saprophytic candidal blastospores that selectively colonize oral, gastrointestinal, vaginal, and cutaneous epithelium. Candida albicans has been regarded as the most common causative agent in human fungal infections. However, other Candida species have become a significant cause of infection. Scanning electron microscope (SEM) observations were used to analyze the capability of C. albicans, C. tropicalis, and C. parapsilosis to adhere to human skin model, used in this study, which was found to mimic the human skin in vivo. The skin sections were inoculated with low and high concentration of the yeasts and followed for 1 and 5 days; then they were viewed by SEM. The electron microscopy observations revealed that all three yeasts tested adhered to the skin but C. albicans covered the entire skin model to a higher extent than C. tropicalis or C. parapsilosis . Mucin-like material coated the blastoconidia mainly in C. albicans . All Candida species have shown characteristics resembling biofilm formation. The use of human skin sections for ex vivo evaluation of adherence of various yeasts may partially explain the predominance of C. albicans in cutaneous pathogenicity.